Formulation and evaluation of paliperidone HCL oral disintegrating tablets - Mohit Kumar; Vandana Arora (International Journal of Pharmacy and Analytical Research, 2022)
Paliperidone HCL is atypical antipsychotic agent which blocks D2, 5HT2, α2, α1 and H1 receptor. It is derivative of Resperidone having better efficacy in treatment of Schizophrenia. When compared with other atypical antipsychotics (eg. Chlorpromazine), it having broad spectrum activity and reduces both positive and negative symptoms of Schizophrenia. It undergoes an extensive hepatic first pass metabolism leads to low oral bioavailability (28%). ODT can overcome this problem through improving its bioavailability with an immediate drug release.In the present work, Oral disintegrating tablets of Paliperidone HCL were prepared by direct compression method using superdisintegrants such as Crosspovidone lycoat, and Tulsion. Paliperidone HCL has very long half hife and less bioavailability, so for enhancing the bioavailability of the drug it was formulated as a oral disintegrating tablet. The dispersion time of tablets were reduced w i t h increase in the concentration of superdisintegrants like Crosspovidone, lycoat, and Tulsion . From the results obtained, it was concluded that Tulsion was found to be the best among the superdisintegrants, the highest drug release of F9 is 99.45% of the drug in 30 min.